A handbook of animals in Old English texts - Preston, Todd (Arc Humanities Press companions., 2022)
A Handbook of Animals in Old English Texts is the definitive handbook for students, scholars, and observers of the non-human in early medieval England. In this interdisciplinary compendium to the animal inhabitants of medieval Britain, Preston documents each creature mentioned in the Old English literary textual canon and correlates its standard literary interpretation with relevant historical, archaeological, and ecological studies. Beyond its usefulness as a reference work, Preston's text challenges the reader to move beyond a literary analysis of the figural beast to one that leaves space for the actual animal."--Provided by publisher.